Sistem Informasi Presensi di SMA Negeri 1 Kepahiang Menggunakan Quick Response Code - Aliana, Mareta; Ikhsan, Arif Rahmat; Oktoeberza, Widhia KZ (Rekursif: Jurnal Informatika, 2023)
SMA Negeri 1 Kepahiang is one of the public high schools located in Kepahiang Regency, Bengkulu Province. The school currently utilizes a manual attendance system, which poses several drawbacks, including the risk of inaccurate data entry and the time-consuming process of cross-referencing individual student/teacher attendance records to identify those who are absent due to illness, leave, or other reasons. The implementation of QR Code technology in the student attendance system is expected to address these challenges and facilitate the recording of attendance data, enabling a faster and more accurate recapitulation process. A system capable of addressing these issues is deemed necessary. The researcher conducted the design of a database, developed User Interface (UI) / User Experience (UX) designs, implemented the system, and concluded with a testing phase. The introduction of this information system is anticipated to streamline and expedite the student attendance process. Keywords: Information System, Attendance, QR Code, Public High School.